Adverse Events Associated With Aesthetic Dermal Fillers: A 10-Year Retrospective Study of FDA Data. Issue 3 (September 2018) - Povolotskiy, Roman; Oleck, Nicholas C.; Hatzis, Christopher M.; Paskhover, Boris
This study investigates the reported adverse events arising with various aesthetic dermal fillers by type and brand name. It reveals rare but dangerous complications associated with a widely used elective procedure. The authors queried and compiled the MAUDE database for injury cases reported with aesthetic dermal fillers between January 2007 and July 2017. A total of 5024 individual cases were then queried for adverse events using specific keywords and grouped into categories for analysis. Categories and keywords were determined after querying a large portion of the samples for common adverse events. The most common complications associated with aesthetic dermal filler use were nodule formation (2952 cases), infection (2575 cases), inflammation (711 cases), allergic complications (594 cases), and vascular complications (590 cases). The most common fillers associated with an adverse event were Juvederm Voluma XC (1050 cases), Sculptra (879 cases), and Radiesse (620 cases). These fillers represent 3 filler types: hyaluronic acid fillers, poly-l -lactic acid fillers, and calcium hydroxylapatite fillers, respectively. Injectable dermal fillers are frequently used cosmetic products around the world. To safely and effectively use these products, health care providers and patients must be fully aware of the proper techniques and risks associated with each product. Many of the complications reported were known to be possible, but others were previously only reported as individual case studies. The rates of occurrence for both well-known and lesser known complications may be higher than originally thought.